Revealing Identity to Form Student Character: Application of the Hidden Curriculum in Islamic Legal Education - Obaid, Yahya; Abidin, Aswar; Samsuddin, Samsuddin; Kadir, St. Fatimah; Baharuddin, Ahmad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Education is one of the most important instruments for forming character and personality. In higher education, especially Islamic law education, curricula serve not only as a means of transferring science but also as a medium for character and moral formation. The study examines the application of hidden curriculum in Islamic law education and its implications for students' character at State Islamic Religious Institute (IAIN) Kendari. Research methods are qualitatively descriptive. Data is obtained through observations, interviews, and documentation. The collected data is processed through data reduction, presentation, and verification, with data validity testing using source triangulation, techniques, and time. The research results show the application of hidden curriculum in Islamic legal education is known through the interaction of faculty-students, Islamic law practice, observance of order and discipline, academic cultural awareness, and extracurricular activities. The values and norms that are indirectly taught in the educational environment have a considerable role in shaping the personality and character of students. The hidden implications of the curriculum for student character formation are manifested in student integrity and ethics, leadership and responsibility, empathy and justice, and the practice of the principles and values of Islamic law in everyday life. Therefore, institutions must integrate hidden curricula into Islamic law education to achieve comprehensive and sustainable educational goals.